The Map of Competencies of a Foreign Language University Teacher in the Context of Digitalization of Education - S. V. Titova (Высшее образование в России, 2022)
Over the past twenty years, a large number of legislative documents, educational standards have been adopted, effective pedagogical models, methods and approaches to teaching foreign languages have been developed at various levels of education in our country and abroad. The article analyzes these documents to describe the current competencies of teachers of foreign languages of higher education. The developed map of competencies of foreign language teachers, which includes digital, professional communicative, methodological and universal competencies, is the result of theoretical research and analysis of the pedagogical experience of distance professional development programs for teachers of foreign languages, designed at the Faculty of Foreign Languages and Regional Studies of Moscow State University named after M.V. Lomonosov. This map can be used as a tool for professional development, since it will allow teachers of foreign languages: to reflect and identify some gaps in their professional development; set short-term and long-term goals; determine the best ways to boost their professional growth; to create innovative models of professional development of teachers, based on a combination of fundamental professional knowledge, professional competencies and skills and assuming the formation of innovative thinking of university employees.